Crimes cibernéticos na pós-modernidade: direitos fundamentais e a efetividade da investigação criminal de fraudes bancárias eletrônicas no Brasil - Aragão, David Farias de (2015)
This study analyzes the criminal investigation of illicit committed in cyberspace, taking into account the context of post-modernity, especially the risk and information society and its impact on the Criminal Law and Criminal Procedure Law, where a strong sense of insecurity experienced in the face of the lack of control of dangers coming from social and technological advances and new conducts that endangers life in community. The aim is to trace the constitutional paradigm to develop a valid criminal investigation in order to reconcile the binomial warranty and efficiency in the exercise of this state activity, using the balancing technique to allow the coexistence of fundamental rights to liberty and the States duty to promote public safety. The network action for illicit behavior in a virtual environment has brought great difficulties to materialize it before the courts and assign responsibility in criminal context, requiring the use of special investigative techniques that sometimes clashes with fundamental rights. After the examination of some of these special investigation techniques that are being applied by the Union s Judicial Police in cases relating to electronic bank fraud, it was found which of those can be applied without preliminary judicial authorization or only after jurisdictional analysis to define in a concrete case the possibility of balancing the investigated person s fundamental right, in particular privacy, and others related to.